Introducing a rat model of prenatal androgen‐induced polycystic ovary syndrome in adulthood. Issue 5 (28th March 2014) - Tehrani, Fahimeh Ramezani; Noroozzadeh, Mahsa; Zahediasl, Saleh; Piryaei, Abbas; Azizi, Fereidoun
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Would it be possible to produce a rat model of polycystic ovary syndrome (PCOS), in which the fetuses are exposed to testosterone for a short time and exhibit both endocrine and ovarian disturbances similar to PCOS, while maintaining normal reproductive system morphology in adulthood? What is the main finding and its importance? Prenatal exposure to a single dose of testosterone during the critical period of fetal development facilitates the production of a functional rat model of PCOS with minimal morphological disorders in adulthood. Production of a functional rat model that resembles many features of PCOS may contribute to a better understanding of this syndrome. Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women, with a prevalence of 8–12% during the reproductive years. In the present study, using prenatal exposure to a single dose of testosterone during the critical period of fetal development, we aimed to introduce an enhanced rat model that would exhibit both endocrine and ovarian disturbances similar to PCOS, while maintaining normal reproductive system morphology in adulthood. Ten pregnant rats were injected s.c. with 5 mg free testosterone on gestational day 20, while control rats received only solvent. The development and function of the reproductive system in female offspring were examined in adulthood. Prenatally androgenized offspring had irregular oestrous cycles compared with control animals, and their anogenital and anovaginal distances were increased compared with control rats (P < 0.001). No significant differences were observed in the lengths of the vagina and clitoris or the number of nipples between the two groups. Levels of testosterone and luteinizing hormone and the luteinizing hormone/follicle‐stimulating hormone ratio were increased in prenatally androgenized offspring compared with control animals (P < 0.05). The numbers of preantral and antral follicles in the ovaries of prenatally androgenized offspring were also increased compared with control rats (P = 0.07 and P < 0.01, respectively). The number of corpora lutea was decreased in prenatally androgenized offspring compared with control rats. Cystic follicles were observed in the ovaries of prenatally androgenized offspring. Prenatal exposure to a single dose of testosterone during the critical period of fetal development could facilitate the development a functional rat model of PCOS in adulthood, with minimal morphological disorders in the reproductive system.